Implementasi Cross Selling Dalam Pemilihan Produk Pada Ecommerce - Reqi Sona (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2020)
The development of technology and the rapid flow of data and information spread on the internet requires the public to know the latest information. To get this information, people generally use search engines or search engines that can facilitate the search for information. Some search engines available on the internet use web crawlers to get the information needed by the user. This research develops a web crawler application to extract information about prices from two comparison sites, the Elevenia site, and the Mataharimall site. The data obtained from the crawling process will be stored in a database which can then be used by the user to see the price comparison of the products sought, then the user can also view the details of the product sought. This system was developed by the waterfall method and displays in Cross-Selling format for the product sought. This research has resulted in crawlers and system applications using cross-selling.